Geometry Skill Analysis In Problem Solving Reviewed From The Difference Of Cognitive Style Students Junior High School - Andi Saparuddin Nur; Evy Nurvitasari (Journal of Educational Science and Technology (EST), 2017)
This study aimed to analyze the geometry skills in solving problems in terms of cognitive styles differences in the students of SMP Negeri Urumb. The type of this research is descriptive research that is qualitative with case study approach. The subject of this research is all students of SMP Negeri Urumb. Subject selection is done by using snowball sampling technique. The main instrument in this study is the researchers themselves and accompanied by supporting instruments such as diagnostic tests, geometry solving test, and interview guides. Validity and reliability of data is done through credibility test, transferability test, dependability test, and confirmability test. Data analysis consists of data collection, data reduction, data presentation, and conclusions. The results of this study were (1) reflective FI subjects showing visual, verbal, drawing, and logic skills with level of geometry thinking at level 2 (informal deduction); (2) impulsive FI subjects exhibiting visual, verbal, and drawing skills with geometric thinking level at level 1 (analysis), (3) reflective FD subjects exhibit visual skills, and draw with level of geometric thinking at level 0 (visualization), and (4) impulsive FD subjects exhibit visual, verbal skills with geometric level thinking at level 0 (visualization).